2006
DOI: 10.1039/b610460f
|View full text |Cite
|
Sign up to set email alerts
|

(2 + 1) REMPI spectroscopy of the NO–CO, NO–N2, and NO–{N2, Ar} van der Waals complexes in the region of the 4s and 3d Rydberg states

Abstract: We have collected (2 + 1) Resonance-Enhanced Multiphoton Ionization (REMPI) spectra of van der Waals complexes in which a NO molecule is attached to either CO, N(2), or both N(2) and Ar. The energy region probed corresponds to electronic transitions of uncomplexed NO(X(2)Pi) to the 4s and 3d Rydberg states, and we discuss the observed spectra in light of the expected perturbations to these electronic levels induced by complexation. We employ a model in which the van der Waals partners are assumed to reside wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The ground state for the N 2 –NO complex has been extensively studied using both electronic structure calculations and experiments. , The overall results for the ground state are consistent with relatively low barriers to internal rotation for the diatomic moieties, resulting in a floppy complex having a minimum geometry with the NO bond approximately perpendicular to the Jacobi vector between the NO center of mass (CM) and N 2 CM. , We henceforth refer to this complex geometry as T-shaped. For the excited state, Lozeille et al performed electronic structure calculations and found nonlinear geometries reverted to the ground state, so only linear excited state geometries were discussed .…”
Section: Introductionmentioning
confidence: 84%
“…The ground state for the N 2 –NO complex has been extensively studied using both electronic structure calculations and experiments. , The overall results for the ground state are consistent with relatively low barriers to internal rotation for the diatomic moieties, resulting in a floppy complex having a minimum geometry with the NO bond approximately perpendicular to the Jacobi vector between the NO center of mass (CM) and N 2 CM. , We henceforth refer to this complex geometry as T-shaped. For the excited state, Lozeille et al performed electronic structure calculations and found nonlinear geometries reverted to the ground state, so only linear excited state geometries were discussed .…”
Section: Introductionmentioning
confidence: 84%
“…The Wright group has made several reports on the N 2 -NO complex. , Mack et al recorded the (1 + 1) resonance enhanced multiphoton ionization (REMPI) spectrum for the N 2 -NO complex . The REMPI spectrum showed that the N 2 -NO band origin lies 55 cm –1 below free NO.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Bergeron et al investigated the (2 + 1) REMPI spectra of the N 2 -NO complex accessed through the 4s and 3d Rydberg states of the NO fragment. The recorded REMPI spectrum of the N 2 -NO complex showed transitions that were assigned to the Ẽ , C̃ , H̃ ′, and F̃ states of the complex …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation